Assessing and explaining local e-government maturity in the Iberoamerican community - Maciel, Gustavo Gouvêa (2020)
This paper assesses local e-government maturity in the Iberoamerican community. Sixty Andorran, Argentinian, Brazilian, Chilean, Colombian, Costa Rican, Mexican, Portuguese, Spanish, and Uruguayan cities were considered in this study. A demographic criterion was adopted to define the municipalities observed within those countries and a three-dimensional model was used to evaluate each municipal website. Then, we conclude that local e-government still has a substantial room for improvement in the region and that population density is relevant to explain local e-government maturity, albeit only in its intrinsic Information and Participation dimensions.